Herdabilidade de alguns caracteres agronômicos de soja nas gerações F₅ e F₆ - Borém de Oliveira, Aluízio; Sediyama, Tuneo; Sigueyuki Sediyama, Carlos; Silva Reis, Múcio; Silva, José Carlos (Revista Ceres, 2025)
The heritability of days to flower, days to maturity, plant and first pod height, lodging, grain yield, seed quality and hundred seed weight were studied in F5 and F6 soybean grown at Vigosa and Capin6polis, in the State of Minas Gerais, Brazil.